Enhanced thermal management in microelectronic cooling: A study on pairing multiple pin-fin shapes in microchannel heat sinks - Kaouthar Madi; Ahmed Raafat; Saeed Al Nuaimi (International Journal of Thermofluids)
In the last decade, microelectronics have advanced significantly, resulting in higher generated heat flux, which, if not managed carefully, may lead to damage or even failure. Pin-fin microchannels are one of the promising techniques that can be used to enhance heat dissipation. This study investigates the thermal and hydrodynamic performance of microchannel heat sinks incorporating different pin fin shapes: square (S), circle (C), and triangle (T). Additionally, various combinations of these shapes, including triangle–square (T–S), triangle–circle (T–C), and triangle–circle–square (T–C–S), were explored to study the effect of combining different shapes on performance metrics. Numerical simulations, validated against experimental data, were conducted under laminar flow conditions for Reynolds numbers ranging from 250 to 1500. The results showed that circular pin fins exhibited a pressure drop 8%–90% lower than other configurations, while square pin fins demonstrated the highest temperature drop along the channel, indicating good thermodynamic performance but at the cost of 90.9% higher power consumption. Triangular pins balanced the thermodynamic and hydraulic performance, with a Nusselt number of 12.6 and a pressure drop 14.4% higher than circular pin fins. Some hybrid configurations combined the advantages of single pin shapes: the T–S arrangement achieved the highest Nusselt number (12.9) with 48.4% lower pressure drop than square pins, while the T–C hybrid maintained a pressure drop close to the circular pin case (8% deviation) while providing high overall efficiency (second best among all configurations). The findings demonstrate that while certain pin shapes perform well individually, hybrid configurations can further enhance the overall performance of microchannel heat sinks.